Melhoria das condições da água utilizando filtro de areia modificado com biomassa - Oliveira, Vanusa Maria Ferreira de (2014)
The development of a region is closely linked to the quality of water available to the population. Thus, water purification techniques are developed to be applied in regions where conventional treatment is not feasible, or even in emergency conditions. In order to combine the reuse of waste materials to water filtration operation, the present study aimed to evaluate the efficiency of sand filters adding biomass of coffee and pine bark, but without subjecting the materials to activation treatments, to remove chemical and physical contaminants from the percolating fluid. PVC filters provided with inner layers of sand and biomass, with were fed with synthetic raw water daily, were built. The filtered samples were analyzed weekly for one month for each employee filling. The results showed that biomass of coffee did not represent an efficient modification for water purification, since it increases the turbidity of the water. While the pine bark, may be an interesting complement for turbidity reduction, especially if the operation time does not exceed 15 days. In addition, both materials showed a tendency to reduce the pH of the water, keeping it within the range of neutrality between 6.0 and 7.0 on average, while the electrical conductivity was high in all tests. Results also showed that, under the adopted conditions, the proposed modification is not feasible, since rather than promoting removal of microorganisms the process, caused contamination of the liquid, probably because the filters were not cleaned during the operation time. Finally, the biomass of pine has a potential use as a supplement to filtering, but in primary treatments, when a subsequent disinfection is performed.